Desain Program Pendampingan Optimasi Remittance Rumah Tangga Tenaga Kerja Indonesia (TKI) di Desa Migran Produktif Mojorejo, Karangmalang, Sragen - Afridah Ikrimah; Beauty Martha Lingga; Ilham Bagus Prasetia; Faris Achmad Baharudin; Mohamad Yogananta; Ernoiz Antriyandarti (Journal of Agribusiness and Community Empowerment (JACE), 2020)
Mojorejo village is one of the productive migrant villages (DESMIGRATIF) in Indonesia. This study aims to determine the alternative way to increase TKI household productivity of through optimization of remittances and to desain a remittance optimization program in building a constructive financial management for TKI households in Mojorejo Village, Karangmalang, Sragen.  This study uses a descriptive analysis with qualitative and systematic review approach.  Data collection techniques were carried out by review the previous research and empowerement, observation through field survey, interview with informan and secondary data searching.  The results show that the problem on increasing TKI household productivity is unoptimal remittance management and it tends to use for consumptive activities.  Lack of public awareness to allocate remittances for investment and productive business causes the stagnant economic growth and does not lead to economic improvement in the surrounding environment. Therefore, remittance optimization can be done through the community empowerment that focus in four activities, namely financial planning training for TKI households, entrepreneurship training and business plan simulations, training in processing, packaging and marketing of rice rambak crackers, and managing mini tourism object of reservoir and selfies of Kembangan Bersolek in  Mojorejo Village, Karangmalang, Sragen.